Political Communication and Candidate Image Construction in Regional Head Elections (Case Study of Sherly Tjoanda's Candidate in The North Maluku Governoral Elections) - Dhyanty Purnamasari (GoResearch - Research & Publishing House, 2025)
This study examines the political communication strategies implemented by Sherly Tjoanda in building her image as a female candidate in the North Maluku gubernatorial election, in a region historically and culturally dominated by male and Muslim leaders. The purpose of this study is to identify and analyze the communication strategies used by Sherly in shaping her political image, and to understand how she overcomes cultural and gender challenges in the local political context. This study uses a qualitative method with a case study approach, through in-depth interviews, observations, and analysis of campaign documents. The results of the study show that Sherly Tjoanda succeeded in building a progressive, communicative, and inclusive political image through three main strategies: (1) personal and inspirational narratives that emphasize Sherly's personal story as a strong woman committed to community empowerment, (2) utilization of social media as a tool to reach young and female voters, and (3) a community and collaborative approach that directly involves the community. This study concludes that effective political communication can play an important role in shaping a candidate's image, especially in the context of regional head elections that are influenced by cultural and gender factors.